Long-Time Behavior of Nonautonomous Fokker-Planck Equations and Cooling of Granular Gases - Lods, B.; Toscani, G. (Ukrains’kyi Matematychnyi Zhurnal, 2005)
We analyze the asymptotic behavior of linear Fokker-Planck equations with time-dependent coefficients. Relaxation towards a Maxwellian distribution with time-dependent temperature is shown under explicitly computable conditions. We apply this result to the study of Brownian motion in granular gases by showing that the Homogenous Cooling State attracts any solution at an algebraic rate.